2014
DOI: 10.1002/chem.201402741
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Tubular Structures Grown from the Gel/Liquid Interface

Abstract: Three dimensional hierarchical materials are widespread in nature but are difficult to synthesize by using self-assembly/organization. Here, we employ a gel-liquid interface to obtain centimeter-long ∼100 μm diameter tubes with complex mineral wall structures that grow from the interface into solution. The gel, made from gelatin, is loaded with metal chloride salt, whereas the solution is a high pH anion source. Tubes were obtained with a range of cations (Ca(2+) , Sr(2+) , Ba(2+) , Cu(2+) , and Zn(2+) ) and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 54 publications
0
26
0
Order By: Relevance
“…Several previous studies have reported the formation and ex situ characterization of calcium carbonate-based tubular structures synthesized by immersion of Ca 2 + -containing salts pellets in Na 2 CO 3 solutions, [13,26,27] or by growth on cationexchange membranes [38,39] and gel/liquid interfaces. [40] However, dynamic diffusion and precipitation processes occurring during the growth and subsequent ripening have not been studied yet in this system. In the present work, we have applied the approaches previously developed for silica gardens [3,10] to monitor time-dependent chemical gradients across tubular CaCO 3 membranes.…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies have reported the formation and ex situ characterization of calcium carbonate-based tubular structures synthesized by immersion of Ca 2 + -containing salts pellets in Na 2 CO 3 solutions, [13,26,27] or by growth on cationexchange membranes [38,39] and gel/liquid interfaces. [40] However, dynamic diffusion and precipitation processes occurring during the growth and subsequent ripening have not been studied yet in this system. In the present work, we have applied the approaches previously developed for silica gardens [3,10] to monitor time-dependent chemical gradients across tubular CaCO 3 membranes.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, precipitate self-assembly can also be made to occur at the interface between cation loaded hydrogels and anionic solutions. 12,13 These systems have also been adapted to accommodate the growth of mineral at non-planar surfaces, such as gel spheres encapsulated with reactant ions. 14,15 Alternatively, the controlled injection of a cationic solution into an anionic reservoir (and vice versa), can provide unique insights into growth regimes during self-assembly and offer greater influence over precipitate composition.…”
Section: Introductionmentioning
confidence: 99%
“…28 In the emerging field of chemobrionics, 21,29 where the spatiotemporal growth of chemical structures are addressed, experimental work on chemical gardens involves reactions of metallic cations most with the use of inorganic materials. [22][23][24][30][31][32][33][34] However, pure organic/hydrogel garden-like structures are still not investigated. The extension from inorganic to organic garden formations is always a challenge for the researchers, and the complete understanding of the underlying mechanism behind these formations is not fully resolved.…”
mentioning
confidence: 99%